Rasionalitas Peternak Sapi Perah terhadap Usaha Ekonomi Desa KUD Sumber Makmur Ngantang : Analisis Perspektif Samuel Popkin - Setiawan, Aldo Wahyu; Mahendra, Afryan Fahri; Aqilla, Ericha Fitri Nuril; Selhbi, Occi Beauty; Hima, Salsa Aslihatul; Arridlo, Dimas Bagus Batoro Alam (Indonesian Journal of Sociology, Education, and Development, 2025)
This study examines the rationality of dairy farmers who are members of KUD Sumber Makmur Ngantang from the perspective of Samuel Popkin's ‘Rational Peasant’ theory. This research uses a descriptive qualitative approach, data collected through participatory observation, in-depth interviews, and documentation of cooperative archives to explore the motives, economic mechanisms, and benefits of cooperative membership. Informants were selected by purposive sampling, including small, medium, and large-scale farmers, as well as cooperative management. Data analysis included data reduction, presentation, and verification with validity testing through triangulation, extended observation, member check, and supervisor consultation. Results showed that dairy farmers rationally joined the cooperative to ensure income stability, access to feed and animal health services, and market certainty through an exclusive partnership with PT Nestlé Indonesia. KUD provides reciprocity in the form of a quality-based milk payment system, savings and loan facilities, feed subsidies, and technical training, which increases income, reduces risk, and strengthens farmers' social capital. These findings reinforce the relevance of Popkin's theory in the context of village cooperatives and affirm the role of cooperatives as motors of local economic development and dairy farmers welfare.